2020
DOI: 10.1111/scd.12492
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis: Update for oral health care providers

Abstract: Systemic sclerosis (SSc), also known as scleroderma, is an autoimmune disease of unknown origin characterized by an uncontrolled inflammatory process resulting in fibrosis of the skin, internal organs and vasculopathy. Manifestations of SSc are heterogenous and can include pulmonary, cardiac, neural, renal, muscular, cutaneous and orofacial complications. Recent scientific advances have led to a better understanding of disease etiopathogenesis and the development of a new classification system. Therapeutic man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 104 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…Basically, it is known that TNF-α, IL-6 or IL-1 are released and attract further B-and T-cell controlled cells, thereby initiating destruction [14]. Although the exact mechanism of the development of SSc remains unclear, it is known that it also develops based on an immune response and affects the vascular system, internal organs and skin with excessive fibrosis and degradation of connective tissue [1,3]. Due to fibrosis of the skin, many orofacial changes also result, especially restricted mouth opening [16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Basically, it is known that TNF-α, IL-6 or IL-1 are released and attract further B-and T-cell controlled cells, thereby initiating destruction [14]. Although the exact mechanism of the development of SSc remains unclear, it is known that it also develops based on an immune response and affects the vascular system, internal organs and skin with excessive fibrosis and degradation of connective tissue [1,3]. Due to fibrosis of the skin, many orofacial changes also result, especially restricted mouth opening [16].…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with limited movement of the fingers and hands and sclerodactyly, patients with SSc suffer from limited oral hygiene ability [26]. Studies have also observed decreased QoL in this context [1,16]. In addition, a recent study showed that patients with dcSSc (n = 28) in particular had a decreased salivary flow rate with reduced pH values, which correlated positively with DMFT and mRSS [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations